An Examination of Texas Agriculture Teacher Safety Attitudes Based on a Personal Belief Scale from Common Safety and Health Practices - Hubert, Dan; Ullrich, Doug (Journal of Agricultural Systems, Technology, and Management, 2003)
Agricultural education programs offer many unique hands-on opportunities to develop both valuable academic and vocational skills for its students. A variety of laboratories provide opportunities for students to actively and experientially engage in scientific inquiry and agricultural applications. In the course of skill development, evidence has suggested students will be more safety conscious if teachers also follow proper safety practices, demonstrate accurate safety knowledge, provide a safe laboratory environment, convey a positive safety attitude, and relay safety expectations to students (Harper, 1984). Positive safety attitudes, beliefs and practices of agricultural science teachers are crucial for insuring students’ educational opportunities are not hampered. This unique study assessed general safety and health perceptions, beliefs, and practices of teachers in Texas agricultural education by means of a Personal Belief Safety Scale (PBSS) score based on common safety and health practices used in agricultural settings. 2 Data was collected from 302, self-selected Texas agriculture teachers, or approximately 20% of all Texas' agriculture teachers in 1999. Results indicated these self-selected Texas agriculture teachers displayed positive agreements toward common measures that exhibit safety consciousness. It was also found that age and years of teaching experience might effect a teacher’s belief or attitude towards agricultural education program safety consciousness. First year teachers and teachers with limited experience appeared more approachable to safety concerns in their programs with female teachers exhibiting a higher conviction towards common safety practices than their male counterparts. Although it was also found that mean PBSS scores by Texas FFA area were significantly different (F=2.13), neither size of school nor the number or students in the agricultural education program had an effect upon teachers’ PBSS scores.